Effects of absorptive capacity and innovation spillover on manufacturing flexibility - Pinheiro, J.; Lages, L. F.; Silva, G. M.; Dias, Á.; Preto, M. T. (International Journal of Productivity and Performance Management, 2022)
Shifting demand and ever-shorter production cycles pressure manufacturing flexibility. Although the literature has established the positive effect of the firm’s absorptive capacity on manufacturing flexibility, the separate role of the innovation competencies of exploitation and exploration in such a relationship is still under-investigated. In this study, we examine how these competencies affect manufacturing flexibility. We use survey data from 370 manufacturing firms and analyze them using covariance-based structural equation modeling (CB-SEM). The results indicate that absorptive capacity has a strong, positive, and direct effect on exploitative and exploratory innovation competencies, proactive and responsive market orientations, and manufacturing flexibility. Our findings also demonstrate that the exploratory innovation competencies mediate the relation between responsive market orientation and manufacturing flexibility. Essentially, these exploitative innovation competencies produce a direct positive effect on manufacturing flexibility while simultaneously being a vehicle for absorptive capacity’s indirect effects on it. An exploration innovation strategy does not significantly affect manufacturing flexibility. This study contributes by combining key strategic features of firms with manufacturing flexibility, while providing new empirical evidence of the mediation of the exploratory innovation competencies in the relation between responsive market orientation and manufacturing flexibility.